Environmental Movements in the United States - Brulle, Robert (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course provides an introduction to the processes of social change, and the key collective actors and institutions that are involved in the creation of U.S. environmental policies. The aim of this course is to provide an understanding of the historical and social processes by which environmental policy is created and changed through a political process among a number of different coalitions. The course starts with an examination of theories of social change. It then examines the development of the various worldviews, organizations, and practices that define U.S. environmental politics, including environmental advocacy organizations and foundations. It concludes with a consideration of the status of the U.S. environmental movement.